Membahas Optimalisasi Pencegahan dan Advokasi Kasus Bullying dalam Pesantren - Shofwan, Arif Muzayin; Purwaningrum, Devia; Farantika, Dessy; Tertibi, Yaoma (Jurnal Konseling dan Psikologi Indonesia, 2025)
Lately, there has been a lot of news about bullying cases in several Islamic boarding schools. This study discusses the optimization of prevention and advocacy of bullying cases in Islamic boarding schools. The data analysis technique uses content analysis by sorting things that are in accordance with the focus and objectives of the study. This study found that bullying is an act that is painful both physically and non-physically from the person who does it to the victim, such as teasing, hitting, kicking, mocking, cursing, gossiping, cursing, shouting, isolating, intimidating, pressuring, discriminating, and ignoring. Ways to prevent bullying in Islamic boarding schools can be done by explaining to students the verses of the Quran that have prohibited bullying. For example, Surah An-Nisa verse 30 prohibits committing violence against others. Surah Al-Hujurat verse 11 prohibits acts of belittling, mocking, and cursing others. There are even many more verses of the Quran that contain prohibitions on bullying. In addition, ways to prevent acts and advocate bullying in Islamic boarding schools can be done with four methods, namely the approach method, the consequence method, the special method, and the activity method. Meanwhile, preventing acts of bullying in Islamic boarding schools can also be done in three ways, namely prevention with spiritual awareness, prevention by maintaining harmony and breaking the cycle of problems, and prevention by eliminating inferior traits and honing assertiveness skills.